Acts of faith : explaining the human side of religion - Stark, Rodney; Finke, Roger, 1954- (University of California Press, 2000)
Finally, social scientists have begun to attempt to understand religious behavior rather than to discredit it as irrational, ignorant, or foolish-and Rodney Stark and Roger Finke have played a major role in this new approach. Acknowledging that science cannot assess the supernatural side of religion (and therefore should not claim to do so), Stark and Finke analyze the observable, human side of faith. In clear and engaging prose, the authors combine explicit theorizing with animated discussions as they move from considering the religiousness of individuals to the dynamics of religious groups and then to the religious workings of entire societies as religious groups contend for support. The result is a comprehensive new paradigm for the social-scientific study of religion.